Estrogenic and anti-proliferative activity of water extract of Glycyrhizzic uralensis (licorice root) - Melissa Poh; Chia Yoke Yin (International Journal of Phytomedicine, 2013)
Licorice is the root of Glycyrrhiza uralensis, which is a commonly used herb in traditional Chinese medicine. Licorice extract has been claimed to have anti-cancer, anti-viral, anti-inflammatory and anti-diabetic activities. This study evaluated the estrogenic effect of licorice root water extract on Ishikawa cells and related it to its effect on cell proliferation using various cell lines in comparison to glycyrrhizic acid (GA). This study showed that licorice root extract exhibited estrogenic property while decreasing cell proliferation thus suggesting possible use in estrogen replacement agent with anti-proliferative property. Even though GA is the most studied active component in licorice, these two properties were not seen in the cell lines tested; hence suggesting that GA is not responsible for these activities. These results showed that licorice could be further studied as an estrogen replacement agent as it does not cause an increase in cell proliferation in the breast and uterus.